Vomiting Induced Pneumomediastinum: A Case Report of a Rare Condition - Saumtally, Mohamed Saad; Masmoudi, Abderrahmen; Zouari, Amine; Talbi, Skander; Harbi, Houssem; Boujelben, Salah (AlQalam Journal of Medical and Applied Sciences, 2022)
Pneumomediastinum is a condition characterized by the presence of free air in the mediastinum and is often a worrisome finding. It can occur spontaneously without any identifiable cause or it can be secondary to a rupture of a hollow organ or due to trauma. Clinical diagnosis is based on symptoms including; chest pain, subcutaneous emphysema, and dyspnea. The diagnosis is confirmed by radiography. On differential diagnosis, esophageal perforation should be considered first, and if suspected, a contrast esophagogram or CT scan should be performed. We present a case of spontaneous pneumomediastinum in a 20-year-old Tunisian male induced by vomiting without esophageal perforation or airway injury.